2007
DOI: 10.1095/biolreprod.106.059394
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Epidermal Growth Factor Receptor/Mitogen-Activated Protein Kinase and Protein Kinase C Signaling in Granulosa Cells from Gallus gallus Are Dependent upon Stage of Differentiation1

Abstract: Studies in both mammalian and nonmammalian ovarian model systems have demonstrated that activation of the mitogen-activated protein kinase (MAPK) and protein kinase C (PKC) signaling pathways modulates steroid biosynthesis during follicle development, yet the collective evidence for facilitory versus inhibitory roles of these pathways is inconsistent. The present studies in the hen ovary describe the changing role of MAPK and PKC signaling in the regulation of steroidogenic acute regulatory protein (STAR) expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…There is also much evidence that cell signaling via the mitogen-activated protein kinase (MAPK) pathway maintains the granulosa layer from prehierarchal follicles in an undifferentiated state [17,18]. In this regard, BMP2 was found to suppress TGFb1-induced FSHR expression, and this inhibitory effect was attributed to enhanced epidermal growth factor receptor ligand (EGFRL) expression and inhibitory MAPK signaling [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is also much evidence that cell signaling via the mitogen-activated protein kinase (MAPK) pathway maintains the granulosa layer from prehierarchal follicles in an undifferentiated state [17,18]. In this regard, BMP2 was found to suppress TGFb1-induced FSHR expression, and this inhibitory effect was attributed to enhanced epidermal growth factor receptor ligand (EGFRL) expression and inhibitory MAPK signaling [19].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of MAPK3/1 signaling partially abolished EGF-or LH-induced oocyte maturation (Reizel et al, 2010;Hsieh et al, 2011) but completely suppressed FSH-induced oocyte maturation in cumulus-oocyte complex (Su et al, 2002). In addition to regulating oocyte maturation, EGF-induced MAPK3/1 signaling also regulates steroidogenesis (Seger et al, 2001;Woods et al, 2007). Other pathways have also been implicated in EGF signaling in the ovary of different species.…”
Section: Introductionmentioning
confidence: 99%
“…Other pathways have also been implicated in EGF signaling in the ovary of different species. EGF has been reported to activate PI3K/Akt in human granulosa cells (Zhang et al, 2010), PKC in the chicken ovary (Woods et al, 2007), and p38 MAPK in ovarian cancer cells (Zhou et al, 2007). To understand the intracellular signaling mechanisms that underlie EGF stimulation of activin subunits in the zebrafish ovary, we undertook this study using pharmacological approach, Western blot and immunohistochemical (IHC) staining, and our results provide evidence that EGF signaling in the ovary involves activin system and it controls the expression of three activin subunits via diverse signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports suggested that AG1478 attenuated FSH-induced actions in ovary from various species. For example, AG1478 augmented FSHR mRNA expression and initiated progesterone production in undifferentiated granulosa cells of chicken ovary (Woods et al, 2007), and blocked meiotic resumption induced by FSH and amphiregulin in mouse cumulus cell-enclosed oocytes (Downs and Chen, 2008). We showed that AG1478 blocked FSHstimulated granulosa cell proliferation.…”
Section: Discussionmentioning
confidence: 64%